Use of non-curative oncological care in osteosarcoma. Issue 28 (1st October 2022) - McMahon, Kevin; Eaton, Vincent; Cichon, Gregory; Griffin, Julia; Dahl, Mary; Silberstein, Peter T.; McKillip, Kate
Abstract : 78 Background: Osteosarcoma is the most common form of bone cancer, but the utilization of palliative care (PC) in patients with this cancer has not previously been investigated in the NCDB. Methods: This study retrospectively evaluated the use of palliative care in osteosarcoma patients diagnosed and recorded in the National Cancer Database (NCDB) between 2004 and 2017. Patients were identified by the International Classification of Diseases for Oncology, Third Edition (ICD-O-3) coding, and patients with other malignancies or missing follow-up data were excluded. Cross tabulations with Chi-square analysis were performed to evaluate frequencies of different patient and tumor characteristics. Multivariable logistic binary regression was performed to evaluate relationships between patient and tumor characteristics and the use of palliative care. Results: A total of 7498 patients were analyzed with 2.8% of all patients diagnosed having any form of palliative care utilization. Of this group, 53.37% received PC within the first 12 months after diagnosis. Those receiving PC were most likely to be treated with non-curative surgery, radiation, chemotherapy, or any combination of these modalities (56.7%). No significant increase in PC utilization was noted over the 13-year duration of this study. Palliative care usage was increased in patients with greater tumor diameter, tumors in the bones of the trunk & skull, or stage IV tumors. Palliative care usage was decreased in patients living 25-49 miles of their treatment facility, those living in pacific states, those with chondroblastic osteosarcoma, or those with private insurance. Conclusions: Palliative care use in patients with osteosarcoma increases with tumor stage, tumor size, or more proximal tumors, but overall utilization remains markedly low. Future studies should further define these patterns of care and help expand the utilization of PC.